Appendix: Brief Chronology of Cendrars. Bibliography of Cendrars's works in English - Monique Chefdor (Studies in 20th & 21st Century Literature, 1979)
Appendix: Brief Chronology of Cendrars. Bibliography of Cendrars's works in English
Keywords: Blaise Cendrars; Chronology of Cendrars; Bibliography of Cendrars